2021
DOI: 10.3892/ol.2021.12537
|View full text |Cite
|
Sign up to set email alerts
|

Time density curve of dynamic contrast‑enhanced computed tomography correlates with histological characteristics of pancreatic cancer

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is characterized by an infiltrative growth pattern with intense desmoplastic stroma comprised of cancer-associated fibroblasts (CAFs). Additionally, the histological characteristics are considered to play a vital role in the poor prognosis of PDAC. However, the density of cancer cells, degree of desmoplasia and vascular proliferation varies in individual cases. We hypothesized that preoperative radiological images would reflect histological characteristics, such as cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 34 publications
(46 reference statements)
0
7
0
Order By: Relevance
“…Comparison of TDCs before and after NAC revealed that δ1′ was significantly higher than δ1 in low-responders. In our previous study, it was revealed that the first slope of TDCs is associated with microvessel density ( 16 ). Even though there were no significant differences in microvessel density between low-responders and high-responders, tumor angiogenesis may have involved the ascent of the first slope of TDC in low-responders.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Comparison of TDCs before and after NAC revealed that δ1′ was significantly higher than δ1 in low-responders. In our previous study, it was revealed that the first slope of TDCs is associated with microvessel density ( 16 ). Even though there were no significant differences in microvessel density between low-responders and high-responders, tumor angiogenesis may have involved the ascent of the first slope of TDC in low-responders.…”
Section: Discussionmentioning
confidence: 99%
“…The histological characteristics of the NAC and non-NAC groups were investigated. The densities of cancer cells, CAFs, microvessels and stromal collagen fibers in the whole areas of the tumor were measured in a way similar to that described in our previous study ( 16 ). In the non-NAC group, the entire maximum cross-section of the tumor was examined.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations